Qualification and disqualification in rape cases - Ekstrom, Simon (Journal of Scandinavian studies in criminology and crime prevention, 2003)
Between 1946 and 1950, the police in Stockholm interrogated almost 150 men about their involvement in alleged rapes and attempted rapes. The results of these investigations eventually led to seventeen prosecutions and eleven convictions. It was not easy to convict someone of rape. However, a consequence of the way the court operated was also that only certain men could be convicted, only certain women regarded as reliable witness, and only certain kinds of attack regarded as plausible. The question of whether the alleged crime was considered possible to prove was dependent upon who reported whom for what. For the complainants it was a matter of qualifying for inclusion within the protection of the law. But what appeared as a rejection of someone's credibility, was in actual fact a result of a prior rejection of the individual's person and character. From the point of view of the legal system, some individuals were more fitted than others for the role of credible victim or likely offender. The sexually immoral woman and the man at the mercy of his sexuality were both in danger of having their credibility questioned: the former a poor victim and the latter all too suitable an offender